FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERBANKAN DI INDONESIA (Studi Empiris pada Bank Umum Persero yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Anis Yunita, 14.05.52.0267; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the factors that affect the financial perfomance of banks (empirical studies on Commercial Bank Limited Listed on IDX Period 2012-2016.Population in this study is Commercial Bank Limited Listed on IDX Period 2012-2016. The financial statement data has been retrieved from IDX which is begun from 1st quarter to 4th quarter in 2012-2016. The analysis tool us in this research is multiple liniear regression.The result of the research show that Good Corporate Governance (GCG) and Net Interest Margin (NIM) has positive significant of Return On Asset (ROA). Non Perfoming Loan (NPL) has negative significant of ROA. Operating Expense / Operating income positive significant of ROA. Loan to Deposit Ratio and Capital Adequacy Ratio has negative significant of ROA.Keywords: ROA, NPL, LDR, GCG, NIM, BOPO, CAR.